The Aftermath of the Peace of Callias - Rung, Eduard; Sapogov, Aleksandr (Anabasis. Studia Classica et Orientalia, 2018)
The paper discusses the history of Greco-Persian relations from the Peace of Callias to the Peace of Antalcidas in the light of recently published book by John Hyland, Persian Interventions: The Achaemenid Empire, Athens, and Sparta, 450–386 BCE (Baltimore: Johns Hopkins University Press, 2018). This is an outstanding work, suggesting some reflections on how ideological doctrines exerted a direct influence on foreign policy and international relations. Of course, one can agree with the book’s author that the imperial ideology of the Achaemenids was inherent in both the period of the great Persian conquests from Cyrus the Great to Xerxes, and the period when the conquering activity of the Persians was declining. However, it is hardly possible to support the author in the opinion that the Persians were not interested in balancing Greeks, and their interferences in interstate relations in Greece were not determined by the desire to support a weaker party against a stronger one. Besides, Hyland does not take into account the obvious fact that the Greeks themselves were ready to deliberately allow the Persians to interfere in their affairs according to their own interests, and, at last, he considers “Greek interventions” as simple interferences in the affairs of Persia.